Agricultural value chain and households' livelihood in Africa: The case of Nigeria - Oluwasogo Adediran; Evans Osabuohien; Magdalene Silberberger; Romanus Osabohien; Waidi Gbenro Adebayo (Heliyon, 2024)
One of the critical issues of concern is how African countries can take agriculture as a business that creates wealth which can help transform rural communities, increase income, reduce poverty and help the continent achieve the United Nations (UN) Sustainable Developments Goals (SDGs) of no poverty (SDG-1) and food and nutrition security (SDG-2) by 2030. Hence, this study examines how participation in agriculture through cassava value chain can improve households' livelihood income in Africa using the case of Nigeria. To achieve its objective, the study utilised quantitative analysis approach to address the linkages among economic agents within the agricultural value chain. The logit regression and propensity scores matching technique are used for the quantitative analysis. The result show that, while more significant proportion of male cassava production household heads sell cassava in its fresh form, their female counterparts add value by processing cassava further into finished staple foods. Another key insight is the high involvement of youth and women in cassava production, processing and marketing. Thus, they have greater influence in promoting and improving households’ livelihood income. Therefore, more targeted efforts should be made by all stakeholders to ensure that youth and women have better, less expensive and dependable assess to facilities at lower interest rates to participate in agricultural value chain. This will engender inclusiveness of the vulnerable groups in agricultural value chain.